What is The Company's Motivation for Doing CSR? An Analysis of Manufacturing Companies - Herianto, Rizka Oktavia; Alfiana, Balqis Zulvina; Apriliyanti, Farshella; Nurcahyono, Nurcahyono; Jatiningsih, Dyah Ekaari Sekar; Wijayanti, Provita (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2023)
Disclosure of CSR in Indonesia is still relatively low. Several companies in Indonesia Empirically, this research examines various factors that motivate companies to disclose CSR. We use profitability, earnings management, leverage, and foreign ownership predictors. The unit of analysis used was 104 of 52 manufacturing companies in Indonesia, the unit of analysis was selected using purposive sampling. Testing between variables with multiple linear regression. The study results show that the more significant profit the company generates will encourage it to disclose CSR as a form of responsibility and maintain its image. Then, a high level of debt will reduce the amount of CSR disclosure because the company has a burden component that must be paid. Lastly, earnings management and foreign ownership are not predictors of companies conducting earnings management.